Juego Educativo en comunidades afrodescendientes: Comprensión etnometodologica a niños y niñas de 7 a 8 años. - Mayorga González, Jose Miguel (2022)
The objective of the study was to understand the practices and methods of the educational game as a pedagogical strategy in children from seven to eight years old in an Afro-descendant context in the municipality of Tumaco, Nariño. It arises from the referents of socio-critical theory as a pedagogical framework that seeks to overcome the verticality of teaching from different readings of the immediate world. The related and achieved analyzes are then presented from conceptual categories such as: educational game, pedagogical strategy, educational game as a pedagogical strategy, psychosocial development in children from 7 to 8 years old and Afro-descendant context. The results found through the implementation of analyzes from ethnomethodology allow the understanding of practices and methods in relation to the socio-critical positions of authors such as Paulo Freire, Viveros and Sánchez, among others, who propose pedagogical models in accordance with the search for social transformation, from the generation of awareness and the dialogue of knowledge.